PEMAHAMAN MANUSIA MENURUT PANDANGAN SUNNI DAN SYI’AH - Andri Afriadi; Badarussyamsi; Feri Nopriansa; Diago Armando Guru Singa; Ermawati (Journal Khafi : Journal Of Islamic Studies, 2023)
In this research, the author is very interested in taking the title of research on human beings and their pre-conceptual nature of Sunni and Shia, the research will discuss the differences in religious views, scholars, philosophical scientists and human beings according to Sunni and Shia views. If observed more deeply about the nature and character of human beings who have an orderly language, have the ability to speak, think and so on, there are a lot of human traits that we need to observe, especially according to the Sunni and Shia understanding. journals, articles, research reports, and other written sources. Especially it will be taken from the Sunni and Shia perspective master book. The Shia understanding does not focus on the concept of perfect man, but according to them man achieves moral and spiritual perfection by serving Allah Swt. More precisely, their teachings on ahlul bayt, in this concept their understanding is more about man seeking their truth, trusting the twelve imams as the inheritors of knowledge and being an example for man in achieving their spiritual and moral goals. This study analyzes the comparison between Sunni and Shia perspectives by focusing on the differences in views and hadiths about human beings and their traits contained in the master books of each of these schools.